Martial arts participation and externalizing behavior in juveniles: A meta-analytic review. (May 2016) - Gubbels, Jeanne; van der Stouwe, Trudy; Spruit, Anouk; Stams, Geert Jan J.M.
Abstract: Martial arts are very popular among juveniles all over the world, but the relation between martial arts and externalizing behavior in juveniles remains unclear. The current multilevel meta-analysis of 12 studies, including 94 effect sizes and N  = 5949 juveniles, was conducted to examine the relation between martial arts participation and externalizing behavior in juveniles, and to examine factors with a possible moderating effect. Results showed that there was no overall relation between martial arts participation and externalizing behavior in juveniles. However, a trim-and-fill procedure implicated publication bias of studies reporting that juvenile martial artist showed more externalizing behavior than non-martial artists, suggesting that the current overall outcomes might underestimate externalizing behavior in martial artists. Moderator analyses showed that studies published in higher impact factor journals, and studies with a higher training intensity in martial arts found more externalizing behavior in martial artists. Furthermore, karate was found to be less related to externalizing behavior than judo. Finally, in comparison with non-athletes and team sport athletes, martial artists showed similar levels of externalizing behavior, but they showed more externalizing behavior when compared to individual sport athletes. Implications for future policy and research are discussed. Highlights: Overall martial arts participation was not related to externalizing behavior. Unfavorable effects of martial arts may be underestimated in scientific research. Type of martial arts moderated the relation with externalizing behavior. Martial artists showed more externalizing behavior than individual sport athletes. No difference in externalizing behavior compared to team sport- or non-athletes.